Age and Gender Specific Characteristics of Hospitalized Patients with Burn Injuries (Medical Forum Monthly, 2024)
Objective: Age and gender is an important risk factor of burn injury. The aim of this study is to determine the relationship of age and gender with other possible risk factors of burn injuries, like educational status, mechanism and intent of burn injury.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at Burns Centre of Civil Hospital Karachi from 2013 to 2014.Materials and Methods: 154 hospitalized patients with burns were sequentially interviewed . Information about age, gender, mechanism of burn injury, intent of burn injury and educational status was collected by questionnaire.Results: High proportion of self-inflicted accidental electrical burn injury was found in young and male patients. Univariable stage showed that prevalence of electrical burn injury was higher in young age group (93.3%) and male patients (100%) as compared to chemical, flame/fire and scald/contact. However, the prevalence of self-inflicted accidental burn injury was also higher in young age group (86.4%)and male patients (100%) as compared to patients with burn injury accidentally by other, deliberately self-harm and assault with significant p value.Conclusion: People who are young and male are more prone to have self-inflicted accidental electrical burn injury while people who are old and female are more likely to have scald/contact related burn injury due to assault.